2014
DOI: 10.1080/1360144x.2014.940956
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of the graduate certificate in academic practice (GCAP) programme

Abstract: Graduate teaching assistants (GTAs) and postgraduates in the UK are taking on greater responsibility for teaching, and therefore it has become increasingly necessary to explore the teacher training that supports them in this endeavour. This paper outlines an impact evaluation carried out on a graduate certificate programme primarily aimed at GTAs and support staff at a research-intensive institution. The concept of impact evaluation is explored. This qualitative research establishes impact on the approaches pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…An increase in the use of student-centred approaches has been documented among faculty members participating in teaching development in other studies (e.g., Gibbs & Coffey, 2004;Postareff, Lindblom-Ylänne, & Nevgi, 2007). Greater reflection and increased adoption of studentcentred teaching approaches were also found in a qualitative study on the impact of TA training in the UK (Chadha, 2015). Critical reflection is a key characteristic of studentcentred teaching and is an important precursor to changes in practice (Brookfield, 1995).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…An increase in the use of student-centred approaches has been documented among faculty members participating in teaching development in other studies (e.g., Gibbs & Coffey, 2004;Postareff, Lindblom-Ylänne, & Nevgi, 2007). Greater reflection and increased adoption of studentcentred teaching approaches were also found in a qualitative study on the impact of TA training in the UK (Chadha, 2015). Critical reflection is a key characteristic of studentcentred teaching and is an important precursor to changes in practice (Brookfield, 1995).…”
Section: Discussionmentioning
confidence: 69%
“…Previous research on TA development program impact. Although research on the impact of TA training programs is slowly growing, the majority of studies have relied on small samples (e.g., Chadha, 2015;Hardré & Burris, 2010;Step-Greany, 2004) and self-report measures. In order to get more nuanced descriptions of the TA development process, recent studies have started to incorporate data from multiple sources, including: feedback on TA teaching from instructors, students, and peer trainers (Rolheiser et al, 2013); changes in student grades after TA training (Hughes, 2014); control groups; and changes in the teaching philosophies of graduate students as a result of training (White, Syncox, Heppleston, Isaac, & Alters, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of teacher training for Graduate Teaching Assistants (GTAs), both as induction into UK Higher Education (UKHE) (Muzaka, 2009) and as long-term development (Chadha, 2015;Sandi Urena et al, 2011), is a topic of long-standing research interest (Beaton & Gilbert, 2013;Park, 2002;Winter et al, 2017). Our study concentrates specifically on where international GTAs experience 'cultural bumps' and 'adjustment stresses' (Wu & Hammond, 2011) to UKHE.…”
Section: Introductionmentioning
confidence: 99%
“…There is a recognized need for teaching assistant training in post-secondary institutions (Chadha, 2015;Love Stowell et al, 2015). Studies have identified several positive outcomes of participating in teaching and learning development, including greater awareness and interest in different teaching practices (e.g., Ash et al, 2009), greater confidence and self-efficacy (e.g., Brancaccio-Taras et al, 2016), and a shift towards student-centred teaching (e.g., Derting et al, 2016).…”
mentioning
confidence: 99%